Factors associated with long‐term HIV pre‐exposure prophylaxis engagement and adherence among transgender women in Brazil, Mexico and Peru: results from the ImPrEP study - Kelika A. Konda; Thiago S. Torres; Gabriela Mariño; Alessandra Ramos; Ronaldo I. Moreira; Iuri C. Leite; Marcelo Cunha; Emilia M. Jalil; Brenda Hoagland; Juan V. Guanira; Marcos Benedetti; Cristina Pimenta; et al. (Journal of the International AIDS Society, 2022)
Abstract Introduction The HIV epidemic continues to disproportionately impact Latin‐American transgender women (TGW). We assessed factors associated with long‐term pre‐exposure prophylaxis (PrEP) engagement and adherence among TGW enrolled in the Implementation of PrEP (ImPrEP) study, the largest PrEP demonstration study in Latin America. Methods HIV‐negative TGW aged ≥18 years reporting 1+eligibility criteria in the 6 months prior to enrolment (e.g. sex partner known to be living with HIV, condomless anal sex [CAS], transactional sex or having a sexually transmitted infection [STI]) who could safely take PrEP were enrolled. Follow‐up visits were conducted at 4 weeks and then quarterly. We conducted logistic regression to identify factors associated with long‐term PrEP engagement (3+ follow‐up visits in 52 weeks) and complete self‐reported adherence (no missed pills in the past 30 days) during follow‐up. For both outcomes, we constructed multivariable models controlling for country, socio‐demographics, sexual behaviour, substance use, STIs and self‐reported adherence at 4 weeks (long‐term engagement outcome only). Results From March 2018 to June 2021, ImPrEP screened 519 TGW, enrolled 494 (Brazil: 190, Mexico: 66 and Peru: 238) and followed them for 52 weeks. At baseline, 27.5% of TGW were aged 18–24 years, 67.8% were mixed‐race and 31.6% had >secondary education. Most, 89.9% reported CAS, 61.9% had >10 sex partners and 71.9% reported transactional sex. HIV incidence was 1.82 cases per 100 person‐years (95% confidence interval [CI]: 0.76–4.38). Almost half of TGW (48.6%) had long‐term PrEP engagement, which was positively associated with reporting complete adherence at week 4 (aOR:2.94 [95%CI:1.88–4.63]) and was inversely associated with reporting CAS with unknown‐HIV partner (aOR:0.52 [95%CI:0.34–0.81]), migration (aOR:0.54 [95%CI:0.34–0.84]), and being from Mexico (aOR:0.28 [95%CI:0.14–0.53]). Self‐reported adherence was associated with TGW aged >34 (aOR:1.61 [95%CI:1.10–2.34]) compared to those aged 25–34 and those with >secondary education (aOR:1.55 [95%CI:1.10–2.19]) and was lower among TGW from Peru (aOR:0.29 [95%CI:0.21–0.41]) or reporting PrEP‐related adverse effects (aOR:0.63 [95%CI:0.42–0.92]). Conclusions Although TGW were willing to enrol in ImPrEP, long‐term PrEP engagement and complete self‐reported adherence were limited, and HIV incidence remained relatively high. A successful HIV prevention agenda should include trans‐specific interventions supporting oral PrEP and exploring long‐acting PrEP strategies for TGW.